Ochicanthon fernandoi: a replacement name for the primary junior homonym O. vazdemelloi Latha and Sabu 2011 (Coleoptera: Scarabaeidae: Scarabaeinae) - Sabu, Thomas K.; Latha, Mathews (Zootaxa, 2011)
Ochicanthon vazdemelloi Latha & Sabu 2011, a wingless new species of dung beetle, was described from the tropical montane cloud forests in the Western Ghats, India (Latha et al. 2011). Authors named the species after Fernando Z. Vaz-de-Mello (Universidade Federal de Mato Grosso, Cuiaba, Brazil). However, we discovered after publication that this species name was a primary junior homonym of another Ochicanthon species from Sumatra: Ochicanthon vazdemelloi Ochi, Kon & Hartini, 2009 (Ochi et al. 2009). Hence, Ochicanthon fernandoi Sabu & Latha, new name is here proposed as a replacement name for Ochicanthon vazdemelloi Latha & Sabu 2011.